STEFANO CATUCCI, FEDERICO DE MATTEIS (eds.) - The Affective City. Spaces, Atmospheres and Practices in Changing Urban Territories - Frediani, Daniele (ZARCH, 2023)
Stefano Catucci, Federico De Matteis (eds.)The Affective City. Spaces, Atmospheres and Practices in Changing Urban TerritoriesSiracusa: Lettera Ventidue, 2021. 352 pp. Tapa blanda. Idioma: inglés. 20,00 €ISBN: 9788862425308